Implementation of the Aladin Program for Repairing Uninhabitable Houses in Jatiblimbing Village, Dander District, Bojonegoro Regency - Linda Tri Andini; Arundinasari, Indira; Hidayat, Endik (Borong Newinera Publisher, 2024)
A decent house is a dream for all people to have a healthy and safe life. Bojonegoro Regency has many uninhabitable houses, especially those owned by the poor. This has become the focus of the Bojonegoro Regency Government to overcome the problem of uninhabitable houses by forming the Aladin Program. The purpose of this research is to find out the Implementation of the Aladin Program to Repair Uninhabitable Houses in Jatiblimbing Village, Dander District, Bojonegoro Regency. This research uses descriptive qualitative research. The focus of the research uses David C. Korten's program implementation theory with three elements, namely the program, implementing organization and target group. Data collection techniques were carried out by means of interviews, observation, and documentation. The data analysis technique used the Miles and Huberman interactive model. The results of this study indicate that the implementation of the Aladin Program in Jatiblimbing Village has been implemented quite well although there are still some obstacles in the program elements and target group elements.